Sites of Tissue Factor Pathway Inhibitor (TFPI) and Tissue Factor Expression under Physiologic and Pathologic Conditions - Østerud, Bjarne; Bajaj, Madhu S; Bajaj, Paul S (Thrombosis and Haemostasis, 1995)
Under normal conditions, TFPI expression is restricted to megakaryocytes and the endothelium of the microvasculature. It is not synthesized by normal hepatocytes or by the endothelium of larger vessels. In contrast, endothelium and peripheral blood cells do not express tissue factor under normal conditions. Expression of tissue factor under normal physiologic conditions is widespread and is localized in areas which are physically separated from the circulating blood. During an inflammatory response, circulating monocytes have been shown to express tissue factor, whereas in general, expression of tissue factor has not been observed in the endothelium. Adherent monocytes/macrophages express both tissue factor and TFPI under pathologic conditions. Whether or not circulating peripheral blood monocytes under inflammatory conditions express TFPI is not known.